Alternative Management of Cushing' Syndrome During Covid-19 Pandemic - Covantev, Serghei; Volkov, Stanislav I.; Samsonova, Kristina I. (Coronaviruses, 2022)
Cushing's syndrome results from prolonged exposure to glucocorticoids. Surgery is often the first-line treatment for this condition, regardless of etiology. However, the COVID-19 pandemic caused a decrease in surgical procedures due to the risk of infection transmission. There are still emergency cases of Cushing’s syndrome that are admitted to the hospital and require urgent management. The current treatment should be focused on medical management and endovascular embolization in selective cases. Embolization can be performed in facilities where there aretrained personnel with experience in adrenal embolization. Surgery, which traditionally is a first-line therapy, can increase the risk of infection, therefore, it should be avoided. The current review provides a brief description of the possible options for the management of adrenal Cushing’s syndrome during the COVID-19 pandemic.
Keywords: adrenal steroidogenesis inhibitors